2021
DOI: 10.1016/j.ebiom.2021.103565
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal overexpression of NOS1AP promotes endophenotypes related to mental disorders

Abstract: Background Nitric oxide synthase 1 adaptor protein (NOS1AP; previously named CAPON) is linked to the glutamatergic postsynaptic density through interaction with neuronal nitric oxide synthase (nNOS). NOS1AP and its interaction with nNOS have been associated with several mental disorders. Despite the high levels of NOS1AP expression in the hippocampus and the relevance of this brain region in glutamatergic signalling as well as mental disorders, a potential role of hippocampal NOS1AP in the pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Our previous studies have also consistently suggested the involvement of CAPON in anxiety modulation [17,23]. However, Freudenberg et al found that CAPON overexpression in dorsal hippocampus had no effects on anxiety related behaviors [34], which may be due to the differential contribution of hippocampus along the dorsoventral axis to the anxiety regulation [35,36]. Therefore, present study was performed to explore 5-HT is an ancient, evolutionarily conserved neurotransmitter for emotional and cognitive processing that is synthesized and released by 5-HTergic neurons, which are primarily located in the raphe nuclei [6].…”
Section: Discussionmentioning
confidence: 63%
“…Our previous studies have also consistently suggested the involvement of CAPON in anxiety modulation [17,23]. However, Freudenberg et al found that CAPON overexpression in dorsal hippocampus had no effects on anxiety related behaviors [34], which may be due to the differential contribution of hippocampus along the dorsoventral axis to the anxiety regulation [35,36]. Therefore, present study was performed to explore 5-HT is an ancient, evolutionarily conserved neurotransmitter for emotional and cognitive processing that is synthesized and released by 5-HTergic neurons, which are primarily located in the raphe nuclei [6].…”
Section: Discussionmentioning
confidence: 63%
“…In DDAH1-ko rats a reduction of NO in whole brain homogenate has been shown (Zhao et al 2021 ). In addition, Freudenberg et al associated hippocampus-specific alterations in NO levels with social and working memory impairments but not with other phenotypes, highlighting that brain-region-specific effects in the machinery regulating NO synthesis may govern the manifestation of specific behaviors (Freudenberg et al 2021 ). Therefore, assessing global and region-specific NO levels in the brain of DDAH1-ko mice and accordingly targeted DDAH1 activity modulation in different brain regions should be essential next steps to increase our understanding of DDAH1 function within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is a critical integration center for learning and memory [ 38 ]. Recent research has revealed that there are abnormalities in the hippocampus in ASD patients from childhood to adolescence [ 39 ].…”
Section: Discussionmentioning
confidence: 99%